The Effects of Folic Acid on Testicular Histology, Sperm Quality, and Spermatogenesis Indices Following 3,4-Methylenedioxymethamphetamine Exposure in Adult Male Rats - Iman Rad; Arezoo Saberi; Najmeh Sadat Koochakzadeh-Nematollahi; Victoria Habibzadeh; Ehsan Salarkia; Sedigheh Amanollahi; Saeideh Nikpour (Addiction and Health, 2021)
Background: There is an increasing concern over acute exposure of amphetamine and its derivative such as3,4-methylenedioxymethamphetamine (MDMA) on male reproductive toxicity. Supplementary vitamins canreduce the oxidative stresses and repair the damages on reproductive organs. This experimental study wasconducted to evaluate the effects of folic acid (FA) on reproductive indices, the antioxidant enzyme activities,and histological changes of testis on adult male rats treated by MDMA.Methods: This experimental study was conducted on adult male Wistar rats. Animals were divided into 4groups: control, MDMA, FA, and MDMA + FA. Animals received a dose of 10 mg/kg of MDMA and 1 mg/kg ofFA for 7 or 14 days. Rats were anesthetized and sperm quality parameters (number, concentration, motility,and morphology), spermatogenesis indices [the mean seminiferous tubule diameter (MSTD), spermiogenesisindex (SI), repopulation index (RI), and tubular differentiation index (TDI)], changes on testicular structure,antioxidant enzyme activities of catalase (CAT), superoxide dismutase (SOD), and malondialdehyde (MDA)beside serum level of luteinizing hormone (LH), follicle-stimulating hormone (FSH), and testosterone weremeasured. Data were analyzed, using the one-way analysis of variance (ANOVA) and SPSS software.Findings: MDMA (both 7 and 14 days) caused significant changes in sperm quality (P < 0.001),spermatogenesis indices (P < 0.001), testicular histopathology, and level of LH, FSH, testosterone beside theantioxidant enzyme activities (SOD, CAT, and MDA) (P < 0.001). Supplementation of FA in association withMDMA partially reversed these parameters and made them close to the control group.Conclusion: The results suggested that FA could reduce the adverse effect of MDMA on reproductive ability inadult male rats.